Cluster Screening: An Effective Approach for Probing the Substrate Space of Uncharacterized Cytochrome P450s. Issue 16 (23rd September 2013) - von Bühler, Clemens; Le‐Huu, Priska; Urlacher, Vlada B.
Abstract Cytochrome P450 monooxygenases (P450s) are versatile enzymes with high potential for biocatalysis. The number of newly annotated P450 genes has been increasing constantly, and these thus represent a rich resource for new biocatalysts. However, the substrate scopes of newly identified P450s are often not known, and thus their exploitation is difficult. Herein we describe an approach, named "cluster screening", and its application for the primary characterization of two P450s: CYP154E1 and CYP154A8. A library comprising 51 compounds was designed and organized into nine groups according to their chemical properties. The activities of both P450s in vitro were maintained with suitable nonphysiological redox partners, and the cluster library was screened with these enzymes for product formation. From this library, 30 compounds tested positive for CYP154E1 and 23 were positive for CYP154A8. Cluster screening distinguishes subtle differences in activity and selectivity of enzymes as closely related as those of the same P450 family. For example, the alkaloid pergolide mesylate was converted by CYP154E1 (4 %) but not by CYP154A8. A building block of vitamin D3, Grundmann's ketone, was converted by both enzymes, although conversion was higher with CYP154E1 (100 vs 53 %).